Performance Measurement at Universities: Systematic Literature Review - Betavia, Ade Elsa; Sanusi, Ahmad; Muda, Iskandar; Ade Kusuma, Sambas (Journal of Social Science, 2023)
The success of a university is influenced by the implementation of performance measurement. Performance at the university can be seen in terms of finance and non-finance. One of the most widely used indicators to determine the success of a university is in its research dimension. Where rankings are based on research to assess the performance of a university do not reflect the overall quality of the university as in the field of teaching. For this reason, it is necessary to apply performance measurements that can assess several existing dimensions, one of which is the balanced scorecard (BSC) approach. By applying the right performance measurement, eating will be able to create improvements in all fields that lead to the realization of Good University Governance. This literature aims to present information about performance measurement at universities both in terms of measurement indicators and what methods are used in performance measurement. The constraints and benefits of performance measurement are also described in this literature. Lack of understanding of the purpose and process of using the Performance Measurement System is the biggest obstacle in the successful implementation of university performance measurement. Pressure from external parties such as stakeholders and cultural differences within the university make performance measurement not work properly.